Analisis Pengaruh Kesejahteraan Ekonomi Terhadap Pernikahan Dini di Indonesia Tahun 2021 - Ferdiana, Rezi; Bachtiar, Nasri; Ariyanto, Edi (Fakultas Syariah INSURI Ponorogo, 2023)
Child marriage at an early age has negative impacts, especially for women, including significant impacts on reproductive health and the economy. Based on data from the Ministry of Religion (Kemenag) for 2021, there are around 2.4 million annually in Indonesia. This study uses the theory of Family Economic Welfare with 8 variables. The data used in this study is data sourced from the results of the March 2021 National Socioeconomic Survey (SUSENAS) using the STATA 12 and SPSS 25 data analysis methods. This study uses logistic regression on 659,261 respondents from all over Indonesia, among whom are categorized as prosperous and 71,701 respondents as not prosperous, based on each respondent's monthly income compared to the national poverty line. The results of this study explain that there is a significant influence between the variables of early marriage, area of residence, number of household members, gender, school participation, last education, home ownership, and sources of information that have a significant influence on welfare. Partially, early marriage has a significant influence on welfare. So, accepting H1 or the independent variable (early marriage) in this logistic regression model partially or individually significantly influences the dependent variable (welfare). Partially, economic welfare has a significant influence on early marriage. This is indicated by the p-value of the early marriage variable, which is 0.000, which is less than 0.05. Low early marriage requires extreme efforts from the human self and interaction with the environment and government support, so collaboration between community groups and the government is needed.